EP1023 The effect of surgery on patients with stage III ovarian cancer and enlarged supradiaphragmatic lymph nodes. (1st November 2019) - Weitzner, O; Yagur, Y; Kadan, Y; Fishman, A; Zissin, R; Ben Ezry, E; Beiner, M
Abstract : Introduction/Background: Enlarged supradiaphragmatic lymph nodes (ESDLN) in patients with advanced epithelial ovarian cancer (EOC) are associated with poor prognosis. This study assessed whether the prognosis is also affected by the treatment approach and surgical outcomes among these patients. Methodology: A retrospective cohort study comparing patients with Stage 3 EOC and ESDLN to those without SDLN, who underwent surgery at a single center from 2006 to 2016. CT scans were retrospectively reviewed by the same radiologist for disease extent and ESDLN. Extent of disease at diagnosis (defined by carcinomatosis score), results of surgery, and progression-free survival (PFS) were recorded. Results: Based on imaging, among 71 women who met the inclusion criteria, 47 (66%) had ESDLN and 24 (34%) did not. There was no significant difference between groups in baseline characteristics except for elevated CA125 at diagnosis in the ESDLN group (1, 797 U/ml vs. 708 U/ml, p=0.04). There was a trend toward longer PFS in the negative SDLN group (19.6 months vs. 12.6 months, p=0.09). Although not significant, among patients who underwent complete cytoreduction, those without ESDLN had longer PFS compared to patients with ESDLN (21.9 vs. 13.6 months, p=0.29). Similarly, a trend toward better prognosis was observed in the negative SDLN group when comparing treatment modalities (21.5 vs. 15.1 months for primary surgery, and 16.5 vs. 9.7 months after neoadjuvant chemotherapy and interval debulking, p=0.16). Conclusion: ESDLN in patients with advanced EOC are associated with poor prognosis. In seems that even when optimal intra-abdominal cytoreduction is achieved, whether at primary surgery or after neoadjuvant chemotherapy, PFS is compromised in patients with ESDLN. Disclosure: Nothing to disclose.